An exploratory study evaluated the 30 most commonly reported medications in the United States food and drug administration’s adverse event reporting system that are associated with the occurrence of kidney stones - Bao, Erhao; Yang, Yang; Jiang, Binglei; Wang, Ben; Liu, Ying; Yang, Lin; Xia, Long; Zhu, Pingyu (Frontiers in Pharmacology, 2024)
This research aimed to identify and analyze the top 30 drugs most commonly associated with kidney stone formation using data from the U.S. Food and Drug Administration's Adverse Event Reporting System (FAERS) database. The study focused on determining the reported Odds Ratio (ROR) and Proportional Report Ratio (PRR) of each identified drug to assess its potential risk of contributing to kidney stone development for effective global burden reduction. Kidney stones are a prevalent urinary system disease influenced by various factors, including medications. Drug-induced kidney stones currently represent 1-2% of all cases, contributing significantly to the overall prevalence. Understanding which medications may trigger stone formation is crucial for managing and reducing this global health issue. Data from January 1, 2010, to March 31, 2024, was extracted from the FDA FAERS database and analyzed. The top 30 drugs associated with kidney stone formation were ranked based on ROR and PRR values. Atazanavir (ROR 46.35, PRR 44.9), Topamax (ROR 19.44, PRR 19.19), and Prevacid (ROR 12.67, PRR 12.57) were the top three drugs associated with kidney stones. Antiretroviral drugs, proton pump inhibitors, and antiepileptic drugs were the most common drug categories linked to kidney stones. Understanding the risk and frequency of drug-induced kidney stones can help reduce patient susceptibility. Clinical vigilance during diagnosis and treatment, along with patient risk communication, is essential in managing this issue effectively.